Plant salt-tolerance mechanisms - Deinlein, Ulrich (2014)
Crop performance is severely affected by high salt concentrations in soils. To engineer more salt-tolerant plants it is crucial to unravel the key components of the plant salt tolerance network. Here we review our understanding of the core salt-tolerance mechanisms in plants. Recent studies have shown that stress sensing and signaling components may play important roles in regulating the plant salinity stress response. We also review key Na+ transport and detoxification pathways and the impact of epigenetic chromatin modifications on salinity tolerance. In addition, we discuss the progress that has been made toward engineering salt tolerance in crops, including marker assisted selection and gene stacking techniques. We also identify key open questions that remain to be addressed in the future.